The Impact of Vocational Education on the Value Added of Industrial and Service Sectors in the European Union and the United Kingdom - Latovic, Jasmin; Bilgin, Murat; Musa, Oriola; Yılmaz, Kadir (International Journal of Economics and Financial Issues, 2025)
This research aimed to analyze the impact of vocational high schools on value added in industrial and service production. In the study, the services value added and industry value added parameters from the World Bank for the EU and the UK for the period between 1970-2023 were taken as dependent variables. Results showed that effect of vocational school pupils per secondary school pupils were negative and significant (B=-0,302; p<0.05) in the EU. In the UK, effect of vocational school pupils per secondary school pupils was insignificant, and educational expenditures had positive and significant contribution on service value added (B=2,579; p<0.01). In the EU, effect of vocational school pupils per secondary school pupils were positive and significant (B=0,372; p<0.01) on industry value added. In the UK, effects of vocational school pupils per secondary school pupils (B=0,061; p<0.05), educational expenditures (B=-4,055; p<0.01) and unemployment (B=1,053; p<0.01) were significant on industry value added. The EU has traditional vocational training institutions that are unable to respond adequately to modern production and industrial facilities, or have not been modernized sufficiently. Vocational training has a significant impact on industrial and service added value, and the direction of this impact is variable.